REVITALISING INDONESIAN ISLAMIC BANKING PERFORMANCE: A STAKEHOLDER ANALYSIS - Ruspita Rani Pertiwi; Jann Hidajat Tjakratmadja; Hary Febriansyah (Bank Indonesia, 2021)
This paper examines the views of Islamic bank stakeholders, which are used as basis for measuring and improving bank performance. Taking Indonesia as a case study, we compile information and data from both internal and external stakeholders through in-depth interviews and focus group discussions, code them using N-Vivo, and finally apply the stakeholder management framework for the data analysis. The results obtained suggest that internal stakeholders’ views of Indonesian Islamic banking performance are relatively positive. However, external stakeholders tend to have varied views of its performance. The research finds that the religious values ​​promoted by Islamic banks can increase company value, but at the same time they can also reduce interest in Islamic banking. Based on these findings, it is necessary to investigate further how to strategise the religious values for the promotion of Islamic banking.